Contamination and impact of organotin compounds on the Brazilian coast - Dos Santos, Dayana Moscardi; Sant'Anna, Bruno Sampaio [UNESP]; Locateli Godoi, Ana Flávia; Turra, Alexander; De Marchi, Mary Rosa Rodrigues [UNESP] (My University, 2012)
Organotin compounds have been extensively discussed worldwide. In Brazil, since 2001 several studies have evaluated organotins in abiotic and biotic matrices, and the results indicate that there is still cause for concern. Because of their hydrophobic behavior, sediments are the main focus of organotin pollution monitoring in risk areas in marine environments. Studies have assessed surface sediments from intertidal and infralittoral areas, shipping channels, harbors, docks, and other impacted areas of estuarine systems, where the behavior and distribution of butyltin compounds may differ, influencing their bioavailability and consequent impact on the biota. The amount of input and estuarine dynamic processes can influence these behaviors, and the study of suspended particulate matter (SPM) has proved to be important to determine the extent of this risk. Because of the wide variability of concentrations, as a result of different factors acting on adsorption and degradation processes, it is suggested that sampling strategies use composite replicates to determine the real concentrations in affected areas. The quantification procedures for all matrices in Brazilian estuaries involve mainly GC-PFPD analysis using the Grignard reagent as the derivative agent, and the results can be considered according to the quality control systems. In addition to sediments, environmental monitoring has also been carried out through quantification of OTs in tissues of mollusks, crustaceans, fishes, and cetaceans. The endocrine disruption caused in mollusks, which results in a condition termed imposex that can lead to the disappearance of populations in certain areas, is commonly used in TBT pollution monitoring. Studies of assimilation and depuration of tributyltin by some organisms are also considered here. In spite of the total ban in 2008, antifouling paints based on tributyltin are still available to artisanal fishers in Brazil, because these paints remain easily accessible and because they are more efficient and have a more persistent effect than the present alternatives. The lack of effective monitoring and public-education policies in Brazil contributes to the continuation of this environmental problem, which can affect estuarine ecosystems and their human communities that depend on local marine resources. © 2011 by Nova Science Publishers, Inc. All rights reserved.